Iran and post-9/11 world order : reflections on Iranian nuclear programme - Alam, Anwar, 1966- (New Delhi : New Century Publications, 2009)
Contributed articles presented in a one-day seminar in February 2008.
Includes bibliographical references and index.
Keywords: Nuclear industry -- Iran; Security, International; Nuclear nonproliferation -- Iran; Nuclear arms control -- Iran; Nuclear weapons -- Iran; Iran -- Politics and government -- 1997-